2004
DOI: 10.1291/hypres.27.971
|View full text |Cite
|
Sign up to set email alerts
|

Spironolactone in Combination with Cilazapril Ameliorates Proteinuria and Renal Interstitial Fibrosis in Rats with Anti-Thy-1 Irreversible Nephritis

Abstract: Blockade of the renin-angiotensin system has been established as a treatment for heart failure with hypertension and left ventricular hypertrophy, and for progressive kidney diseases. The present study was con-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 25 publications
1
11
0
1
Order By: Relevance
“…Available evidence supports the use of aldosterone antagonists in patients with proteinuria not adequately controlled by ACE inhibitors or ARBs and in patients with chronic kidney disease (CKD) [ 9 ]. Those results have also been observed in experimental animal models with GN [ 10 – 12 ]. The previous findings led us to hypothesize that aldosterone plays a role in the development of glomerular injury and the increased proteinuria seen in patients with GN.…”
Section: Introductionsupporting
confidence: 70%
“…Available evidence supports the use of aldosterone antagonists in patients with proteinuria not adequately controlled by ACE inhibitors or ARBs and in patients with chronic kidney disease (CKD) [ 9 ]. Those results have also been observed in experimental animal models with GN [ 10 – 12 ]. The previous findings led us to hypothesize that aldosterone plays a role in the development of glomerular injury and the increased proteinuria seen in patients with GN.…”
Section: Introductionsupporting
confidence: 70%
“…In another experimental model, Asai et al (29) reported that combination therapy with spironolactone and cilazapril in anti-Thy-1-antibody-induced nephritis in uninephrectomized rats ameliorated proteinuria and renal interstitial fibrosis. These findings suggest that chronic combination therapy may be a potentially useful treatment for hypertensive rats.…”
Section: Fig 7 Comparison Of Aldosterone Infusion In the Absence Anmentioning
confidence: 99%
“…The present data suggest that increased aldosterone due to "aldosterone escape" could be another important contributor to renal fibrosis because aldosterone interacts synergistically with TGF-ß to increase PAI-1 overexpression and subsequently inhibit ECM degradation. If it acts in vivo, this synergistic effect may explain the beneficial effects of combination therapy with an Ang II blocker and an aldosterone blocker that have been observed in patients with heart failure, diabetic nephropathy and nephritic range albuminuria (11,44,46,49) and in animal models with hypertension and glomerulonephritis (2,31,41).…”
Section: Synergistic Effect Of Tgf-1 and Aldosterone On Ecm Degradatimentioning
confidence: 99%